Verheerliking en die kruis? Die Johannese herinterpretasie van die kruis as δόξα - Van der Watt, JG (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
The cross events in the Gospel according to John are often described as the glorification of Jesus. This is a Johannine reinterpretation of the reality of the cross. This article describes how John presents the cross events as the opportunity for Jesus to reveal his own identity through his divine actions. His identity is acknowledged and confessed by his disciples, which results in his glory. It is also argued that John does not deny that the cross events might also be interpreted differently, but that he wants to present the events in the light of the glory of Jesus.